Pesca, alimentação, reprodução e crescimento do Amuré, Gobioides broussonnetii Lacepède, 1800 (Pisces : Gobiidae) no Estuário Amazônico, município de Vigia - Pará - BRAGANÇA, Alexandre José Machado (Universidade Federal do Pará, 2013)
Gobioides broussonnetii, the largest species of the family Gobiidae, is found in the western Atlantic Ocean, from the United States to Rio Grande do Sul, Brazil. It is abundant in the Amazon River estuary where it is typically found in the brackish waters of mangroves. Besides being an important link in the Amazon estuary food web, this species is a resource exploited by local fishermen. Fishing practices, diet, reproduction, and growth of Gobioídes broussonnetii were studied in Marajó Bay, municipality of Vigia, Pará state, Brasil, between September of 2003 and August of 2004. Specimens were obtained from local fishermen and information about fishing practices for this species were obtained through field-observation and from interviews with fishermen. The diet was studies by means of based on 314 specimens. Reproductive aspects included the period of reproduction and the size at first maturation of 749 specimens. Growth parameters were estimated using the indirect method based on the total lengths of 1155 specimens. Gobioides broussonnetii, known locally as "amure" in the Amazon River estuary, is captured on the muddy bottom in shallow water and is used as bait in commercial fishing. In general, the species is phytophagous, and stomach contents analyses showed the algae Coscinodiscus concinus to be most abundant food item Larger amount of food in the stomachs were recorded during the dry season (July to December). The reproductive period for G. broussonnetii in the study area ranged from January to June_ The mean length of the first gonadal maturation was 23,9 cm. The observed sex ratio was 1:1 (X²= 0,834, P<0,001). Results obtained in this study indicate that G. broussonnetii uses the Amazon estuary as an spawning, nursery, and feeding area. Macroscopic examination of the gonads indicated that the reproductive season tanges from January to June, although there is a single spawning per year, from February to April. Nine age groups of G. broussonnetll were found in the Amazon estuary. Estimates for growth parameters were obtained as follows: L∞ = 67,36 ( K=0,205 ano-1, Ø = 3,014). The length-weight relation was significantly different between males and females, with females heavier than males.